“Peer teaching program using ecrif and pdp frameworks to improve speaking and listening skills in the first level of the pedagogic English major at the technical University of Cotopaxi.” - Gavilanes Pilatasig, Grecia Mishel (2022)
Speaking and listening are fundamental skills that English students must master to become competent users. In particular, in the context of teaching English as a Foreign Language (EFL), such us the first English Major where many students face several problems when developing the above-mentioned skills due to the low English level. That’s why the present project was carried out to describe experiences in the implementation of the peer teaching program using ECRIF and PDP frameworks with the pre-service teacher and students at the Technical University of Cotopaxi. The ECRIF means Encounter, Clarify, Remember, Internalize and Fluency to helps students to speak and the PDP framework means Pre-listening, During-listening and Post-listening to provide effective listening lessons. The researcher applied a qualitative research survey with open-ended and closed-ended questions that were used as data collection for students. The reflection guide was used also as an instrument to collect data for pre-service teacher. Five first term students of English Major at Technical University of Cotopaxi were the population. The main findings showed positive and negative aspects. The positive results were that by implementing this program using the ECRIF and PDP frameworks 80% of students were able to improve their speaking and listening skills through different techniques applied (guessing games, role plays and collaborative work). In that case, 80% of them felt that this program contributed to their learning. However, they considered that this program should be applied in face-to-face classes instead of virtually. So, 60% of them felt very satisfied with the material implemented, while 40% of them felt comfortable. Conversely, the pre-service teacher faced some drawbacks such as lack of class participation, lack of time management for the activities, unknown vocabulary for the students and as a student’s suggestion, the didactic materials could be improved by using more technological tools. Moreover, the pre-service teacher's experiences during the implementation were both positive and negative. She gained experience in teaching English and preparing activities with these frameworks. As negative points, she was unable to give clear instructions and the didactic material had an unfamiliar vocabulary for the students which impeded them to develop the activities. Based on these findings, the researcher suggests strengthening the present project by including it in the curricula to provide a better learning experience for students.